Knowledge Attitude and Practices as Barriers to Tuberculosis Case Finding in the Ga District - Koray, H.I. (University of Ghana, 1999)
This study was designed to determine the barriers to tuberculosis case-finding in the Ga district with respect to the knowledge, attitudes and practices of individuals in the population. The Ga District is located in the Greater Accra Region of Ghana with a population of 246,552. 184 questionnaires were administered on subjects drawn from the general population. Focus Group Discussions were also conducted to explore the underlying factors for the health seeking behaviour of the people. Respondents comprised 59.7% (110) females and 40.3% (74) males. 56.5% (104) had only primary education whilst 27.2% (50) had no formal education. 9.8% (18) were familiar with the disease, 70.1% (129) knew it was curable, but only 51.6% (94) knew that treatment was available and free. Cough with bloodstains and weight loss are well known signs and symptoms of TB in the Ga district. Causes as perceived by the people included getting it through the air, and from smoking cigarettes. TB is generally believed in the district to be severe and fatalistic. It is the second most stigmatized disease in the district and ranks only next to HIV/AIDS. It was found that the people mostly seek treatment at the local health centre, however using health facilities, like the Korle-be Teaching Hospital, outside the district is not uncommon. Results of the study indicated insufficiencies in the knowledge of TB in the Ga district and this was found to be the major factor affecting TB case-finding in the district. There will therefore be the need for the DHMT to undertake a major Information Education and Communication (IE&C) campaign in order to create awareness and reduce the myths and misconceptions people have about TB in the general population. Special educational material should be provided to the Ministry of Education so that all pupils who go through the formal educational system are given some information on tuberculosis. There is the need for programme managers to emphasize on interpersonal communication especially in the local languages since the general level of education in the district is low. Churches are good places to start educational campaigns in the district.